The Determinants of Tourist Visiting Interest in Sade Village Tourism Central Lombok - Lahuri, Setiawan Bin; Putri, Sri Firda Rahmi Aliya; Sup, Devid Frastiawan Amir; Saleh, Muhammad Aunurrochim Bin Mas'ad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research aims to find out the influence of Destination Image and Service Quality on tourist Visiting Interest with Halal Attributes as intervening variables, as the determinants of tourist Visiting Interest in Sade Village Tourism Central Lombok. The increase in the Muslim population in the world has made halal tourism an increasingly important global phenomenon, considering the changing interest of tourists in a more holistic tourism experience based on religious values. Lombok is the only Indonesian region with the first Regional Regulation (PERDA) about halal tourism. This research is quantitative research with a Structural Equation Modeling (SEM) approach using SmartPLS software (v.3.2.9) with 97 respondents used as a sample. Data analysis techniques are used descriptive analysis, outer model measurement, inner model measurement, and hypothesis test. The result is, first, that Destination Image positively and significantly affects Visiting Interest. Second, there is no positive or significant influence of Service Quality on Visiting Interest. Third, Destination Image and Service Quality positively and significantly influence Visiting Interest in Sade village tourism through Halal Attributes. The implication is, first, the academics and policymakers should constantly monitor, evaluate, and complete all shortcomings in the facilities and infrastructure of Sade village tourism. This can provide comfort and satisfaction for the local community or tourists and increase the interest in tourist visits. Second, the practitioners (Sade village tourism managers) must continually improve the quality of services and infrastructure that can support tourists' needs, providing satisfaction that can later impact an increase in tourist visits.